Optimization of Sulphur Requirement to Sesame (Sesamum indicum L.) Genotypes Using Tracer Techniques (Bangladesh Journal of Botany, 2012)
Four sesame genotypes viz., T6, SM4, SM7 and SM8 were verified with three levels of sulphur 10, 20 and 40 kg/ha including control. Factorial experiment was laid out in a completely randomized design with four replications. Biochemical parameters such as chlorophyll, nitrate reductase, amino acid and total sugar in leaves, total dry mass production, total nitrogen accumulation in seeds and seed yield increased with sulphur application up to 20 kg S/ha. Application of 40 kg S/ha had no significant benefit on biochemical parameters, dry matter and seed yield of sesame though 35S uptake in seeds increased with increasing sulphur levels till 40 kg/ha. The biochemical traits and nutrients uptake were superior in SM4 than other genotypes which resulted in the highest seed yield of SM4. Among the sulphur levels, 20 kg S/ha showed the maximum seed yield in all the genotypes. Therefore, sulphur @ 20 kg/ha can be recommended for getting maximum productivity of sesame genotypes. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11076 Bangladesh J. Bot. 41(1): 7-13, 2012 (June)